Pengembangan Automatic Pet Feeder Mengunakan Platform Blynk Berbasis Mikrokontroller ESP8266 - Heri Ngarianto; Alexander Agung Santoso Gunawan (Engineering, MAthematics and Computer Science Journal (EMACS), 2020)
In this paper, automatic pet feeder device was developed. This device is useful for feeding pets at home when all family members are busy working or traveling. The device settings can be controlled by the mobile application automatically, thus the pet owners can ensure the feeding of their pets. The development of this tool is based on an electronic board which uses an ESP8266 microcontroller namely WeMos D1 MINI and is equipped with a Relay Shield to control the amount of food released. In addition, through Blynk platform, the pet owners can control this device remotely. Pet feeding also can be done according to a schedule that can be pre-arranged as needed in realtime.